2020
DOI: 10.1080/02687038.2020.1781419
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the components of a successful spoken naming therapy: a meta-analysis of word-finding interventions for adults with aphasia

Abstract: Background:Spoken word retrieval therapy forms an integral part of aphasia therapy. Due to the range of therapy options and variations, drawing clear-cut conclusions from the evidence base can be challenging. Aims:This paper consolidates recent findings (2008 -2018), pertinent to spoken word-finding interventions. Specifically, we are interested in aphasia interventions : (1) that target singleword spoken naming; (2) whose participants are adults with acquired naming impairments after a stroke; and (3) whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 110 publications
1
8
0
Order By: Relevance
“…Moreover, as per previous work in our lab [ 34 , 44 , 45 , 46 , 47 ] and following the original protocol [ 20 ], frequency and dosage (3 times per week for 5 weeks total, approximately 60 min sessions) ensure the feasibility of Fr-PCA in the clinical practice in Quebec. Moreover, these therapy variables correspond to optimal variable ranges in terms of minutes per session [ 65 , 66 ], the number of sessions weekly [ 65 , 66 ], and cumulative dosage [ 66 ] reported in previous studies on naming therapies that improve naming performance in persons with aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as per previous work in our lab [ 34 , 44 , 45 , 46 , 47 ] and following the original protocol [ 20 ], frequency and dosage (3 times per week for 5 weeks total, approximately 60 min sessions) ensure the feasibility of Fr-PCA in the clinical practice in Quebec. Moreover, these therapy variables correspond to optimal variable ranges in terms of minutes per session [ 65 , 66 ], the number of sessions weekly [ 65 , 66 ], and cumulative dosage [ 66 ] reported in previous studies on naming therapies that improve naming performance in persons with aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…Today, this is one of the approaches to therapy for naming disorders. Studies of phenomena such as central nervous system repair, cortical reorganization after brain damage, and the improvement of language function by behavioral therapy, support the view that patients may regain lost capabilities by extensive training (e.g., Dietz & Ward, 2020;Ping Sze, Hameau, Warren, & Best, 2021). Also, studies have provided evidence that upregulation of attentional control contributes to recovery of language after stroke (e.g., Geranmayeh et al, 2017), which is confirmed in a meta-analysis of the literature (Stefaniak et al, 2021; but see Wilson & Schneck, 2021).…”
Section: Wernicke's Model and Wundt's Critiquementioning
confidence: 93%
“…Several reviews and meta-analyses have identified that training words in anomic aphasia results in improved retrieval of these words (but generally does not extend to untrained vocabulary, which is less problematic in this case) (Wisenburn & Mahoney, 2009). More recent work has identified some specific effective components of these interventions, such as presenting written words along with the spoken form (Sze, et al, 2021). This approach could easily be implemented within number-word training interventions.…”
Section: Support Coping Strategies and Self-trainingmentioning
confidence: 99%